2013
DOI: 10.1128/iai.00546-13
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia Encodes a Type II Protein Secretion System That Promotes Detrimental Effects on Lung Epithelial Cells

Abstract: The Gram-negative bacterium Stenotrophomonas maltophilia is increasingly identified as a multidrug-resistant pathogen, being associated with pneumonia, among other infections. Despite this increasing clinical problem, the genetic and molecular basis of S. maltophilia virulence is quite minimally defined. We now report that strain K279a, the first clinical isolate of S. maltophilia to be sequenced, encodes a functional type II protein secretion (T2S) system. Indeed, mutants of K279a that contain a mutation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…Mutants used in this study are also listed in Table 1. S. maltophilia strains were routinely cultured at 37°C on Luria-Bertani (LB) agar (Becton, Dickinson, Franklin Lakes, NJ) or LB broth (21). In order to obtain supernatants for enzymatic assays and other analyses, S. maltophilia strains were cultured in a version of buffered yeast extract (BYE) broth consisting of 10 g per liter of yeast extract, 54.9 mM N-(2-acetamido)-2-aminoethanesulfonic acid buffer, and 39.2 mM potassium hydroxide at pH 6.85 to 6.95.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mutants used in this study are also listed in Table 1. S. maltophilia strains were routinely cultured at 37°C on Luria-Bertani (LB) agar (Becton, Dickinson, Franklin Lakes, NJ) or LB broth (21). In order to obtain supernatants for enzymatic assays and other analyses, S. maltophilia strains were cultured in a version of buffered yeast extract (BYE) broth consisting of 10 g per liter of yeast extract, 54.9 mM N-(2-acetamido)-2-aminoethanesulfonic acid buffer, and 39.2 mM potassium hydroxide at pH 6.85 to 6.95.…”
Section: Methodsmentioning
confidence: 99%
“…By constructing and characterizing gsp and xps mutants of the clinical isolate K279a, we concluded that Xps T2S promotes detrimental effects on the human lung epithelial cell line A549. Specifically, S. maltophilia supernatants caused cell rounding, detachment, and actin rearrangement and exhibited cytotoxicity of A549 cells in an Xps T2S-dependent manner (21). It remains to be determined whether Gsp T2S is functional, as gsp mutants do not lack any of the observed activities exhibited by strain K279a.…”
mentioning
confidence: 98%
See 3 more Smart Citations